PERIOPERATIVE ASSESSMENT OF CHEMILUMINESCENCE INDICATORS OF LYMPH NODES IN TONGUE CANCER - Sh. I. Musin; R. R. Farkhutdinov (Креативная хирургия и онкология, 2017)
The high frequency of regional metastasis of oral cancer in the lymph nodes in the neck forms need to find new methods of informative assessment of lymph nodes of the neck. One of the promising methods for assessment of lymph node status is to study free radical oxidation by detecting chemiluminescence. The study of dynamics of chemiluminescence – the perioperative evaluation - allows us to estimate the depth of irregularities in the system of "free radicals- antioxidant protection." The rate of change of perioperative indicators chemiluminescence is a prognostic factor. The study of perioperative indicators chemiluminescence in 25 primary patients with cancer tongue has done. A slight change in the chemiluminescence (Δ chemiluminescence not more than 20.5%) is unfavorable.